Political Participation of Disability Organizations in Inclusive Elections: Evidence from Perkumpulan Sehati in Sukoharjo Regency, Indonesia - Alfiah Nur Hidayani; Martien Herna Susanti (Universitas Negeri Semarang, 2025)
Inclusive elections represent a fundamental principle of democratic governance by ensuring equal political rights for all citizens, including persons with disabilities. However, disability political participation remains constrained by institutional, social, and accessibility barriers, while the role of disability organizations in facilitating electoral inclusion has received limited scholarly attention. This study aims to analyze the political participation of Perkumpulan Sehati as a disability organization in supporting inclusive elections in Sukoharjo Regency during the 2024 General Election. A qualitative case study approach was employed using in-depth interviews, observations, documentation, and triangulation techniques to explore organizational participation and structural challenges. The findings indicate that Perkumpulan Sehati contributed to electoral mobilization, community-based political education, and institutional collaboration with election management bodies, thereby strengthening democratic inclusion for persons with disabilities. Nevertheless, political participation continues to be influenced by limited political education, inadequate polling station accessibility, insufficient family support, social stigma, and low institutional trust. This study contributes to the literature by emphasizing the mediating role of disability organizations as civil society actors in transforming formal political rights into substantive democratic participation. The findings also suggest that collaborative governance involving election organizers, local governments, and disability organizations should be institutionalized to strengthen inclusive electoral governance in Indonesia.